2015
DOI: 10.2106/jbjs.o.00071
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic Osteonecrosis of the Femoral Head: Where Do We Stand Today?

Abstract: ➤ Although multiple theories have been proposed, no one pathophysiologic mechanism has been identified as the etiology for the development of osteonecrosis of the femoral head. However, the basic mechanism involves impaired circulation to a specific area that ultimately becomes necrotic.➤ A variety of nonoperative treatment regimens have been evaluated for the treatment of precollapse disease, with varying success. Prospective, multicenter, randomized trials are needed to evaluate the efficacy of these regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
446
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(465 citation statements)
references
References 303 publications
(320 reference statements)
7
446
1
11
Order By: Relevance
“…The current study attempted to establish a link between THSWD and HIF-1α/VEGF pathways in order to clarify whether THSWD is able to regulate the apoptosis of bone cells. Although the mechanisms SANFH are unclear, the consensus view is that the final result of SANFH is an interruption of bone microcirculation (27), mainly through disruption of angiogenesis and limiting of the penetration of new vessels into necrotic bone (1). Regular angiogenesis is thus crucial to ameliorating SANFH, since angiogenesis is closely correlated with increased circulation of oxygen and nutrients in bone tissues (28).…”
Section: Discussionmentioning
confidence: 99%
“…The current study attempted to establish a link between THSWD and HIF-1α/VEGF pathways in order to clarify whether THSWD is able to regulate the apoptosis of bone cells. Although the mechanisms SANFH are unclear, the consensus view is that the final result of SANFH is an interruption of bone microcirculation (27), mainly through disruption of angiogenesis and limiting of the penetration of new vessels into necrotic bone (1). Regular angiogenesis is thus crucial to ameliorating SANFH, since angiogenesis is closely correlated with increased circulation of oxygen and nutrients in bone tissues (28).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there are no effective preventive measures for SANFH (14). Although multiple theories underlying this complication have been proposed, no pathophysiologic mechanism has been identified as the etiology for the development of osteonecrosis of the femoral head (15). In the present study, the IHC results revealed that Beclin 1 protein expression was increased in the femoral head of SANFH patients, indicating that autophagy was overactivated.…”
Section: Discussionmentioning
confidence: 47%
“…subcondral cysts are seen on both sides of the left joint with mild reactive synovitis while keeping in mind that the natural course of the disease will not be altered [21].…”
Section: -09-2014mentioning
confidence: 99%